Career aspirations in a short-term and long-term aspects among final year dental students in IIUM Kuantan - Roslan, A’isyah; Abu Kasim, Azyan; Mustapa, Anis Zafirah; Che Musa, Muhd Firdaus (2019)
Introduction: The dental workforce in most countries includes Malaysia is facing unprecedented changes with an implication for workforce flexibility and mobility. Therefore, the aim of this study was to investigate both the short and long term career expectations of senior dental students in International Islamic University of Malaysia (IIUM) and its influential factors. Materials and Methods: All 64 final year dental students in IIUM were invited to participate in a self-administered questionnaire survey in 2018. The survey explored both short- and long-term career expectations and demographic background. The Chi-squared test was used to compare career expectations by students demographic. Results: 62 students (97%) completed the questionnaire. The majority were aged 25 years (63%), female (71%), high-income families (38%) and Malays (98%). In the short-term, ‘gain knowledge, skill and experience’ (39%) was the most commonly cited goal; whereas ‘gaining professional experience’ and ‘achieving financial stability’ (73%) were their greatest influences. ‘Having a break from study’ showed significant difference by family income (p=0.03). In the long-term, 73% planned to specialize; whereas 77% considered working full-time with ‘team work with professionals’ (98%) was its main influences. Majority of the respondents were anticipating to work in private sector (66%) with men more likely to do so than women (p=0.04). Conclusions: There was a high level of interest in specialization and a desire to work in a professional team and to achieve financial stability in this group. Career expectations varied by gender and social income but not by age